Phur pa dril sgrub; a collection of Vajrakila rituals performed at the Rdo-rje-brag Monastery and its affiliates throughout Tibet - Rgod-kyi-ldem-ʼphru-can, Gter-ston, 1337-1408 (Smanrtsis shesrig spendzod,, 1973)
Rites of the Nyingmapa sect for the dispelling of evil forces.